2008
DOI: 10.1002/glia.20760
|View full text |Cite
|
Sign up to set email alerts
|

Pituicyte modulation of neurohormone output

Abstract: Pituicytes have long been suspected to play a role in the regulation of neurohypophysial hormone output. This role has been mainly ascribed to morphological changes in these cells and subsequent modifications of their tight structural relationships with surrounding nerve terminals and capillaries. These entirely reversible changes are brought about by physiological states such as parturition, lactation, or dehydration, and it was inferred that they should facilitate neurohormone output, based on concerted anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…Virard et al [44] suggested that the rat NL contains glial progenitors. The pituicyte is also considered an osmotic sensor involved in the neurohypophysis hormone output [45]. The heterogeneity of dromedary NL glial cells, with four different types: light and dark in winter and phagocytic and granular in summer, suggests a relationship between the light type and the protoplasmic pituicyte, and the phagocytic type and a mi- crogliocyte or a subpopulation of pituicytes.…”
Section: Discussionmentioning
confidence: 99%
“…Virard et al [44] suggested that the rat NL contains glial progenitors. The pituicyte is also considered an osmotic sensor involved in the neurohypophysis hormone output [45]. The heterogeneity of dromedary NL glial cells, with four different types: light and dark in winter and phagocytic and granular in summer, suggests a relationship between the light type and the protoplasmic pituicyte, and the phagocytic type and a mi- crogliocyte or a subpopulation of pituicytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, AQP4 in the pituicytes does not seem to accumulate at the perivascular area, suggesting a different function from that in brain astrocytes. Pituicytes show remarkable morphological changes in response to physiological stimuli such as dehydration [8, 23]. Under hypotonic conditions on the other hand, it has been suggested that pituicytes sense hypotonicity, causing taurine release which inhibits vasopressin release from the axon terminal [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pituicytes show remarkable morphological changes in response to physiological stimuli such as dehydration [8, 23]. Under hypotonic conditions on the other hand, it has been suggested that pituicytes sense hypotonicity, causing taurine release which inhibits vasopressin release from the axon terminal [23]. Hence, pituicytes appear to play an important role as osmotic sensors [23] and AQP4 might be necessary for pituicytes to sense hypotonic or hypertonic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This implicates AQP4 water channels in neurohypophyseal neuroglial interactions affecting water homeostasis not only during pathologies such as brain edema but also under physiological conditions. Indeed, pituicytes appear to be key elements in the osmoregulation process (Hussy 2002;Hussy et al 2000): These cells are sensitive to osmolar changes and have been recently described as osmotic sensors (Rosso and Mienville 2009). Possibly, AQP4 in pituicyte plasma membranes is involved in this sensor effect during osmoregulation.…”
Section: Discussionmentioning
confidence: 99%